An Analysis of Affective Factors that Hamper Students’ Participation in English Language Classroom - Mujahidah; Andi Novita Sari Ramadhani; Muhammad Zuhri Dj; Magdahalena Tjalla; Munawir (CSR International Journal, 2022)
Affective is a combination of emotions, feelings, moods, and attitudes that can affect a person from the inside. This research aims to analyse the most dominant aspect of affective factors that hamper students’ participation in English language classrooms and the causes in terms of individual affective factors such as anxiety, inhibition, introversion/extroversion, self-esteem, motivation, learning style, and relational affective factors such as empathy, cross-cultural processes and classroom transactions. This research was conducted on the tenth-grade students at MA DDI Lil-Banat Parepare. The samples of this research were 25 students selected through snowballing sampling technique. This research used a qualitative descriptive to examine the phenomenon under study critically. The instruments used in this research were observations and semi-structured interviews. This research indicates that the dominant aspect of affective factors that hamper students’ participation in English language classrooms is self-esteem. The psychological condition of low self-esteem mostly happens to the students, which occurs to 48% of the sample students. Based on the results of students’ interviews, it is found that low self-esteem was caused by pessimistic about their abilities, lack of self-confidence, and a sense of inferiority.